Rancang Bangun Sistem Informasi Akuntansi Penjualan dan Pembelian Pada Koperasi Karyawan Senayan City Jakarta Menggunakan Metode Waterfall - Kussetiawan, Hertanto Dwi; Kaafi, Ahmad Al; Nurachim, Rusma Insan; Saraswati, Sandra Dewi (Forum Kerjasama Pendidikan Tinggi, 2020)
The Senayan City Employee Cooperative is a cooperative that operates in the field of savings and loans and at the same time manages a shop business unit, buying and selling transactions are only recorded in Microsoft Excel format, when sales transactions are not immediately recorded so mistakes often occur. For this reason, we designed a sales and purchase information system design at the Senayan City Employee Cooperative using desktop-based java NetBeans, with the aim of creating a computerized system so that it could be used by the cooperative management. The software development methodology used in this research includes software requirements analysis, design, code generation, testing, and support. The results obtained from this research are the need for a cash sales accounting information system, cash receipts and sales reports that can assist cooperative managers in making decisions